2020
DOI: 10.1007/978-3-030-64946-3_27
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Halving for Sets of Items

Abstract: Consensus halving refers to the problem of dividing a resource into two parts so that every agent values both parts equally. Prior work shows that, when the resource is represented by an interval, a consensus halving with at most n cuts always exists but is hard to compute even for agents with simple valuation functions. In this paper, we study consensus halving in a natural setting in which the resource consists of a set of items without a linear ordering. For agents with linear and additively separable utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In [Goldberg et al, 2020] the problem under study deviates slightly from the typical consensus halving problem. There are (divisible) items and they are not presented in a linear order, but rather unordered, with agents having linear and additively separable utilities over them.…”
Section: Further Related Workmentioning
confidence: 99%
“…In [Goldberg et al, 2020] the problem under study deviates slightly from the typical consensus halving problem. There are (divisible) items and they are not presented in a linear order, but rather unordered, with agents having linear and additively separable utilities over them.…”
Section: Further Related Workmentioning
confidence: 99%
“…Batziou et al [12] showed that the corresponding strong approximation problem (with measures represented by algebraic circuits) is complete for BU. A version of Consensus-Halving with divisible items was studied by Goldberg et al [46], who proved that the problem is polynomial-time solvable for additive utilities, but PPAD-hard for slightly more general utilities. Very recently, Deligkas et al [30] showed the PPA-completeness of the related Pizza Sharing problem [50], via a reduction from Consensus-Halving.…”
Section: Related Workmentioning
confidence: 99%
“…We are now ready to show PPAD-hardness. To do this, we reduce from a slightly modi ed version of G studied by Goldberg et al [2020], that we call G [−1,1] . is modi ed version operates on and 𝐺 [−1,1] ×−𝜁 (where the gates truncate to [−1, 1], and 𝜁 ∈ [0, 1]).…”
Section: E Ppad and Fixp-completeness Of Generalized Circuit Variantsmentioning
confidence: 99%
“…is modi ed version operates on and 𝐺 [−1,1] ×−𝜁 (where the gates truncate to [−1, 1], and 𝜁 ∈ [0, 1]). Goldberg et al [2020] proved that 𝜀 -G [−1,1] is PPAD-hard for some su ciently small constant 𝜀 > 0. We now set 𝜀 := 𝜀 /50.…”
Section: E Ppad and Fixp-completeness Of Generalized Circuit Variantsmentioning
confidence: 99%